2017
DOI: 10.1002/pros.23313
|View full text |Cite
|
Sign up to set email alerts
|

LuCaP Prostate Cancer Patient-Derived Xenografts Reflect the Molecular Heterogeneity of Advanced Disease an­­d Serve as Models for Evaluating Cancer Therapeutics

Abstract: Background Metastatic prostate cancer is a common and lethal disease for which there are no therapies that produce cures or long-term durable remissions. Clinically relevant preclinical models are needed to increase our understanding of the biology of this malignancy and to evaluate new agents that might provide effective treatment. Our objective was to establish and characterize patient-derived xenografts (PDXs) from advanced prostate cancer (PC) to investigation of biology and evaluation of new treatment mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
308
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 249 publications
(318 citation statements)
references
References 51 publications
9
308
0
1
Order By: Relevance
“…Finally, to assess whether BROMO-10 is able to predict responsiveness of PC to bromodomain inhibitors, we used RNA-seq profiles of panels of PC cell lines and expression array profiles of patient-derived xenografts (PDXs) (Nguyen et al, 2017) to generate BROMO-10 scores (Figure 7 D and E). We then correlated these scores with publicly available IC50 data for JQ1 (Asangani et al, 2016) (Figure 7F), ZEN-3694 (Attwell et al, 2016) (Figure 7G), I-BET762 (Figure 7H), and responsiveness to I-BET762 treatment measured as a significant reduction in tumor volume (Wyce et al, 2013) (Figure 7I).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, to assess whether BROMO-10 is able to predict responsiveness of PC to bromodomain inhibitors, we used RNA-seq profiles of panels of PC cell lines and expression array profiles of patient-derived xenografts (PDXs) (Nguyen et al, 2017) to generate BROMO-10 scores (Figure 7 D and E). We then correlated these scores with publicly available IC50 data for JQ1 (Asangani et al, 2016) (Figure 7F), ZEN-3694 (Attwell et al, 2016) (Figure 7G), I-BET762 (Figure 7H), and responsiveness to I-BET762 treatment measured as a significant reduction in tumor volume (Wyce et al, 2013) (Figure 7I).…”
Section: Resultsmentioning
confidence: 99%
“…This is evident by the low numbers of prostate cancer PDXs in international consortia, including the EurOPDX consortium, JAX Laboratories and BioMedical Research PDX encyclopedia, where prostate cancer PDXs constitute only 1% of the collection in some cases . To address this problem, academic groups developed a repertoire of serially transplantable PDX of prostate cancer, resulting in over 100 authenticated PDXs, including those from the Living Tumor Laboratory, the LuCaP series, the MD Anderson (MDA PCa) series, the Johns Hopkins University cohort, our recently published collection from the Melbourne Urological Research Alliance (MURAL), and others . The take rates for establishing these serially transplantable PDX were 10% to 40% and they often had long latency times of up to 12 months after initial grafting .…”
Section: Introductionmentioning
confidence: 99%
“…As the number of prostate cancer PDXs increases, the process of maintaining them becomes more laborious and time consuming. PDXs are often maintained by continually repassaging them into new host mice, which can be as often as every few weeks for fast growing tumors . Therefore, the ability to store PDXs through cryopreservation would decrease the workload of maintaining them.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to insufficient suppression of the host's adaptive and innate immune systems, this limited success rate could be due to the fact that the previous attempts used either small biopsy samples from metastatic sites or localized prostate cancers from radical prostatectomy specimens which did not allow validation of their aggressive nature (ie, lethality). To allow a more diverse sampling of different lethal metastatic sites, including bone metastases, and to allow a more optimally standardized tissue yield and viability protocol, Robert L. Vessella and Paul H. Lange at the University of Washington, Seattle initiated a rapid autopsy program in the early 90's to harvest lethal prostate cancer tissue from a variety of metastatic sites from each patient . During the period from 1991 to 2005, the University of Washington group collected 261 prostate cancer samples from 156 patients and implanted them subcutaneously into immune deficient intact male mice without Matrigel.…”
Section: Introductionmentioning
confidence: 99%
“…This group later switched to using the more immune deficient scid intact male mice, but again did not use Matrigel co‐inoculation. Eva Corey now leads this program and has reported that 26 xenografts have been successfully propagated beyond three passages …”
Section: Introductionmentioning
confidence: 99%